2015
DOI: 10.1021/acsami.5b04058
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Conductive Gel Network as an Effective Binder for High-Performance Si Electrodes in Lithium-Ion Batteries

Abstract: Silicon (Si) has been widely investigated as a candidate for lithium-ion batteries (LIBs) due to its extremely high specific capacity. The binders play a key role in fabricating high-performance Si electrodes which usually suffer from the huge volume expansion associated with the alloying and dealloying processes. Here we develop a facile route to prepare a three-dimensional (3D) conductive interpenetrated gel network as a novel binder for high-performance Si anodes through chemically cross-linking of acrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…Yu et al presented a3 Dc onductive PAA/PANI interpenetrating polymer network (IPN) by in situ polymerization of aniline (ANI) monomers in the PAA-based hydrogels. [56] As shown in Figure 16, the strong hydrogen bonding between PAAa nd PANI was revealed by the FTIR spectrum peak at 1472 cm À1 , and electrostatic interactions were also formed between the protonated amine groups in PANI and-COO À in PAA. Both the intermolecular hydrogen bonding and ionic bondingcontributed to the stable conductive network, resulting in the Si-based electrode with PAA/PANI reaching ah igh ICE of 89.3 %a nd a high retention capacity of 2205 mAh g À1 after 300 cycles at a current density of 2400 mA g À1 .…”
Section: Polymerbinders With Multi-dynamic Bondsmentioning
confidence: 93%
See 1 more Smart Citation
“…Yu et al presented a3 Dc onductive PAA/PANI interpenetrating polymer network (IPN) by in situ polymerization of aniline (ANI) monomers in the PAA-based hydrogels. [56] As shown in Figure 16, the strong hydrogen bonding between PAAa nd PANI was revealed by the FTIR spectrum peak at 1472 cm À1 , and electrostatic interactions were also formed between the protonated amine groups in PANI and-COO À in PAA. Both the intermolecular hydrogen bonding and ionic bondingcontributed to the stable conductive network, resulting in the Si-based electrode with PAA/PANI reaching ah igh ICE of 89.3 %a nd a high retention capacity of 2205 mAh g À1 after 300 cycles at a current density of 2400 mA g À1 .…”
Section: Polymerbinders With Multi-dynamic Bondsmentioning
confidence: 93%
“…[56] b) FTIR spectraofS i, Si-PAA/PANI, PAA/PANI, and PAA. [56] Chem.E ur.J. 2019, 25,10976 -10994 www.chemeurj.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim voltage windowsa re usually pretty narrow.T he full cells with lithium iron phosphate (LiFePO 4 ), especially lithium nickel-manganese-cobalt oxide (NMC), as the cathodes always require high voltage stability.…”
Section: Conclusion Challenges and Perspectivesmentioning
confidence: 99%
“…Silicon (Si) has received increasing attention as a new negative electrode material with high theoretical capacity (3579 mA h g −1 ) [ 8 ]. Also, silicon has a relatively low voltage plateau, and is non-toxic, inexpensive and abundantly available in nature [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hybridized networks and calcium-mediated cross-linked alginate binders have been used as novel gels for Si slurry. 17 Self-healing polymers via supramolecular interactions have been proposed for Si binders. 18 Wang et al reported a superabsorbent PAA-PVA gel for Si anodes, which effectively accommodated the volume change due to the adhesively transformable polymer network.…”
Section: Introductionmentioning
confidence: 99%